التظاهرات الجلدية عند مرضى البدانة البالغين - خدام, جمال; مطره جي, روان (Latakia University Journal -Medical Sciences Series, 2018)
This study was conducted to define the skin manifestations in obese patients and compare them with a control group of normal-weight patients. A total of 161 obese patients (BMI ≥ 30kg/m²) and 154 normal weight patients (BMI 18.5-24.9 kg/m²) were included in the study. A medical history and demographics information were obtained from all the individuals, with a full dermatological examination and some blood tests. All of them were evaluated for the presence of hypertension, as well as diabetes, dyslipidemia and metabolic syndrome. The dermatoses that showed a statistically significant relationship with obesity, compared with control group were: Plantar hyperkeratosis, Striae distensae, skin infections, fungal and bacterial skin infections, Acrochordons, Cellulite, Pseudoacanthosis nigricans, Psoriasis, chronic venous insufficiency, hirsutism and xanthelasma palpebrarum. Obesity is associated significantly with certain dermatoses, It is essential to detect those dermatoses in obese patients since many of these conditions are treatable, leading to an improved life quality. Also, some of these dermatoses might represent a sign for systemic disease that need to be detected and diagnosed. أجريت هذه الدراسة لتحديد التظاهرات الجلدية عند البدينين ومقارنتها مع مجموعة الشاهد طبيعي الوزن. ضمت الدراسة 161 مريضاً بديناً (BMI ≥30 kg/m²) و154 مريضاً طبيعي الوزن (BMI= 18.5-24.9 kg/m²)، أخذت المعلومات الديموغرافية والقصة السريرية وأجري فحص جلدي كامل وطلبت بعض الفحوصات الدموية. قُيّم كل المرضى من ناحية ارتفاع الضغط الشرياني، السكري، اضطرابات الشحوم والمتلازمة الاستقلابية. الجلادات التي أظهرت أهمية إحصائية مع البدانة مقارنة مع مجموعة الشاهد: فرط التقرن الأخمصي، الفزر الجلدية، الأخماج الجلدية، الأخماج الجلدية الفطرية والجرثومية، الزنمات الجلدية، السيلوليت، الشواك الأسود الكاذب، الصداف، القصور الوريدي المزمن، الشعرانية والصفرومات الجفنية. ترتبط البدانة بشكل واضح مع جلادات محددة ومن الضروري كشف هذه الجلادات عند البدينين لأن العديد منها قابل للعلاج ويحسن نوعية الحياة عند البدينين، كما أن بعض هذه الجلادات قد يكون علامة لمرض جهازي يجب تحريه.